Anthraquinones from leaves of Tectona grandis: A detailed study on its antibacterial activity and other biological properties - Mahesh S. Krishna,; Jayakumaran Nair A, (International Journal of Phytomedicine, 2011)
The search for new molecules against pathogenic species continues unabated due to drug resistance. Tectona grandis, commonly known as teak, is a widespread woody plant with lot of biological properties. In the present study, attempts were made to isolate antibacterial compounds from Tectona grandis against Staphylococcus aureus, Klebsiella pneumoniae, Salmonella paratyphi and Proteus mirabilis at different concentration. Antimycobacterial activity was checked against Mycobacterium tuberculosis. Cytotoxicity of isolated compounds was evaluated. As part of activity studies, antioxidant potential of both compounds was also checked. Antibacterial activity was checked by disc diffusion and microplate dilution method. Cytotoxicity of pure compounds was evaluated by MTT assay. Antioxidant activity was checked against DPPH and ABTS+ free radicals. Two compounds isolated from chloroform extract of leaf showed activity against S. aureus (Compound 1: MIC – 2.5μg/ml, IC50 - 72μg/ml ; Compound 2: MIC - 5 μg/ml, IC50 - 98 μg/ml) and K. pneumoniae (Compound 2: MIC – 6.2 μg/ml, IC50 – 113.5 μg/ml). These compounds failed to show antimycobacterial activity on testing against M. tuberculosis. On cytotoxicity analysis of both compounds against chick embryo fibroblast (CEF), HEK293, HCT119 and L929 cells, compound 2 showed activity against HEK293 (IC50 - 2 μg/ml). Antioxidant activity of these compounds was very low and was able to scavenge only 10% of free radicals even at the highest concentration (1000 μg/ml) tested. Purity of compounds was confirmed by HPLC analysis and structural characterization was carried out based on IR and NMR spectral data with supporting phytochemical results.